Analyzing the Partnership between the U.S. and Albania: Bilateral Agreements and Cooperation for 101 Years - Tomja, Alida; Dumani, Alketa (European Journal of Multidisciplinary Studies, 2023)
This paper aims to provide a comprehensive analysis of the 101-year relationship between the United States and Albania, with a particular focus on bilateral agreements and cooperation. The study begins by examining the historical background of the two countries and their initial interactions, and then proceeds to explore the political and diplomatic relations between the two nations. The main hypothesis of this paper is that the partnership and cooperation between the United States and Albania have been shaped by several factors, including the geopolitical context of the region, the ideological orientations of the two nations, and the institutional frameworks that have been established to facilitate their collaborative efforts. The research question that this paper seeks to answer is: How has the relationship between the United States and Albania evolved over the years, and what are the main factors that have influenced its development? To achieve this objective, the paper adopts a mixed-methods research design that combines a systematic review of existing literature on the topic, with a qualitative analysis of primary sources such as government reports and official documents. The main findings of this paper indicate that the partnership and cooperation between the United States and Albania have been characterized by a number of bilateral agreements and initiatives in areas such as security and defense, energy, and education. While these agreements have helped to strengthen the relationship between the two nations, they have also faced a number of challenges, including corruption, organized crime, and political instability. Despite these challenges, the partnership and cooperation between the United States and Albania remain vital to promoting regional stability and advancing common interests in areas such as security, economic development, and democratic governance. As such, continued engagement and cooperation between the two nations should be a priority in the years to come.